2016
DOI: 10.1089/cyber.2016.0234
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction Among College Students in China: Prevalence and Psychosocial Correlates

Abstract: This study examined the prevalence of Internet addiction among college students in China and explored the correlations between Internet addiction and psychosocial factors. A total of 1,173 Chinese college students (62.1 percent males, Mage = 19.65 years) were invited to complete a questionnaire containing measures of demographic characteristics, psychosocial correlates, including the quality of the parent-child relationship, propensity for depression, and psychosocial competence, and Internet addictive behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 38 publications
4
51
2
2
Order By: Relevance
“…A meta-analysis of 31 nations across seven world regions showed that a global prevalence of IA was estimated at 6.0% [22]. In China, one study among 1173 Chinese college students found that 15.2% were classified as having Internet addiction (IA) [23]; another study have reported that 12% of young smart-phone users (mean age = 26) were classified as probable problematic social networking use [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 31 nations across seven world regions showed that a global prevalence of IA was estimated at 6.0% [22]. In China, one study among 1173 Chinese college students found that 15.2% were classified as having Internet addiction (IA) [23]; another study have reported that 12% of young smart-phone users (mean age = 26) were classified as probable problematic social networking use [24].…”
Section: Introductionmentioning
confidence: 99%
“…One longitudinal study has found that greater use of the Internet was associated with declines in participants' communication with family members in the household, declines in the size of their social circle, and increases in their depression [31]. In China, studies have shown that students who reported poorer parent-child relationships, higher levels of depression, and lower levels of psychosocial competence were more likely to report behaviors indicative of IA [23]. Alternatively, the association between lower level of family support and higher level of depression with smoking has been widely documented [15,16,20,21,32].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, this is due to the conceptual complexity of psychological, pedagogical and sociological studies of the issues related to the use of the Internet environment by primary schoolchildren. However, it should be noted that a negative informational and psychological impact of the Internet on children and adolescents is studied actively enough [16][17][18]. The papers note that children and adolescents are the most vulnerable group of Internet users [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that a negative informational and psychological impact of the Internet on children and adolescents is studied actively enough [16][17][18]. The papers note that children and adolescents are the most vulnerable group of Internet users [18,[20][21][22]. At this stage, the issues of Internet consumption by primary schoolchildren and closely related issues of the impact of information risks and online threats on personal development of children need to be studied, and in addition, science based management of these processes should be provided [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Последние эпидемиологические исследования показывают, что распространенность ИА среди молодежи в Северной Америке и Европе составляет от 1,5 до 13,9% [7][8][9]. В странах Восточной Азии уровень ИА достиг 36,9% среди малазийских студентов [10], 15,6% среди подростков из Гонконга [11], 21,2% во Вьетнаме [12], уровень ИА среди китайских студентов оценивается как 15,2-21,3% [13,14]. Имеются единичные работы, посвященные эпидемиологии ИА в России.…”
unclassified